Pregnancy through assisted reproductive technology in a patient with thoracic endometriosis syndrome - S Krishnakumar; Rohan Krishnakumar; Sonali Hiwale (Wolters Kluwer Medknow Publications, 2018)
Extrapelvic endometriosis is known to be difficult to diagnose. Appropriate management in an infertile patient with extrapelvic endometriosis is not only difficult but also not well established. This case report describes a patient with thoracic endometriosis syndrome who was managed successfully for controlling her pleural endometriosis and achieving a pregnancy through assisted reproductive technology (ART).